Impact assessment of funding on technology acquisition by small businesses: A case study of hair salons in a South African municipality. Issue 1 (31st May 2019) - Madichie, Nnamdi O.; Mpiti, Nosiphiwe; Rambe, Patient
Abstract : Purpose: This study aims to examine the influence of funding on the technology acquisition by small businesses in a metropolitan municipality, Mangaung, which governs Bloemfontein and surrounding towns in the Free State province of South Africa. Methodology/design/approach: A case study using survey research strategy of 110 small businesses in a South African municipality informed the research design for this study. The structured questionnaires were quantitatively analysed yielding both descriptive and regression results to address the research objectives. Findings: The findings suggest that the prime sources of public funding for hair salon businesses are the National Youth Development Agency and the Small Enterprise Development Agency. The results also demonstrate that public funding has a negative and significant impact on technology acquisition, perhaps suggesting the complexity of debt financing and the exorbitant interest rates charged on principals borrowed by foreign nationals. Originality/value: The study recommends the judicious acquisition of inexpensive technologies (e.g. social media platforms) and cautionary utilisation of complex technologies and personal savings before resorting to external borrowing.